Communication—Filtration of Light Emitted from Solid State Incandescent Light Emitting Devices. (1st January 2017) - Zhang, Shumao; Kuo, Yue
Abstract : The broad-band light emitted from the solid state incandescent light emitting device was narrowed down by the addition of an a -Si:H or SiNx thin film. The a -Si:H film strongly absorbed the short-wavelength light of below 600 nm. The SiNx film showed interference effect on incident light, i.e., including peaks in the transmittance spectrum. This effect was dependent on the film's refractive index and thickness, which could be controlled by the deposition condition. The Fabry-Perot filter made of the a -Si:H/SiNx stack could be used to filter the broad-band light into a narrow-band light peaked at 850 nm. There are many applications of the filtered light including the on-chip optical interconnect.